2020
DOI: 10.1002/chem.202003074
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Oxidation States of Dopants: A Strategy for the Modulation of Material Photoluminescence Properties

Abstract: Doped single-phase materials have been widely investigated owing to their easy to implement synthesis and the variety of their properties. This minireview covers strategies for the costabilization and the ratio control of several oxidation states of dopants inserted in the same host. The tuning of the oxidation states of dopants opens up many possibilities for the optimization of specific properties and can be envisioned for various applications such as telecommunication, medicine, display, lasers or lighting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…[ 7–9 ] While facing these challenges, one of the most interesting factors that is mostly overlooked in transition metal‐based SACs is the effect of the oxidation states of the metal atom centers in the precursors. [ 10 ] Despite numerous reports on Fe/N/C‐type catalysts, an in‐depth assessment for the development of a versatile strategy is still required for tuning the kinetic activity of a single FeN 4 site. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7–9 ] While facing these challenges, one of the most interesting factors that is mostly overlooked in transition metal‐based SACs is the effect of the oxidation states of the metal atom centers in the precursors. [ 10 ] Despite numerous reports on Fe/N/C‐type catalysts, an in‐depth assessment for the development of a versatile strategy is still required for tuning the kinetic activity of a single FeN 4 site. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] While facing these challenges, one of the most interesting factors that is mostly overlooked in transition metal-based SACs is the effect of the oxidation states of the metal atom centers in the precursors. [10] Despite numerous reports on Fe/N/C-type catalysts, an in-depth assessment for the development of a versatile strategy is still required for tuning the kinetic activity of a single FeN 4 site. [11] However, it has been established that mixed-valence states in nanomaterials coordinating environment exhibit extraordinarily high catalytic efficiencies due to the synergism among oxidation states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the field of dosimetry through the development of photographic films, Geiger-Muller and proportional counters have experienced continuous and rapid progress [ 15 , 16 ]. The investigation of solutions as standards, as well as the variation in oxidation states and color changes, have been extensively studied [ 17 , 18 ]. However, specific manipulations in addition to heavy and expensive instrumentation such as NMR, IR, UV-Vis spectrophotometer, ESR and thermoluminescence are quite necessary for the detection of changes in these solutions.…”
Section: Introductionmentioning
confidence: 99%
“…al., Mn doped BaAl 2 O 4 's emission color was investigated and it was found that by changing the concentration of the Mn as co-dopant ion, the emission color can be tuned [8]. Researchers observed an enhancement in the luminescence properties of phosphors by doping with Li + ions in order to stabilize the oxidation state of dopant, thereby increasing the luminescence properties [9]. To enhance the luminescence intensity of SrAl 2 O 4 :Eu 3+ , B 3+ phosphors, Li + dopant was used as a charge compensator.…”
Section: Introductionmentioning
confidence: 99%